FORMATION OF SKILLS IN JUNIOR SCHOOLCHILDREN SOLVE STEM MATHEMATICAL PROBLEMS (Pedagogy of Higher and Secondary Education, 2004)
The problem of forming junior pupils' skills to do topic sums is considered in the article.